The Role of Emotion Regulation and Executive Functioning in the Intervention Outcome of Children with Emotional and Behavioural Problems - Blossom Fernandes; Mark Wright; Cecilia A. Essau (Children, 2023)
Emotional and behavioural problems are closely associated with impairments in regulating emotions and in executive functions (EF). To examine this further, the aim of the present study was to determine whether EF and emotion regulation at baseline would predict emotional and behavioural problem scores post-intervention, and further explore the extent to which emotion regulation mediates these outcomes. Participants were 41 primary school children who exhibited emotional and/or behavioural problems, aged 8 to 11 years. All the children completed measures of emotional and behavioural problems, cognitive emotion regulation, anxiety symptoms, and performed two experimental tasks to measure working memory and response inhibition before and after participating in a transdiagnostic Cognitive Behaviour Therapy-based programme, “Super Skills for Life” (SSL), and at 3-months follow-up. Results revealed significant reduction in the use of maladaptive emotion regulation strategy catastrophising and other blame following the intervention. Additionally, EF and emotion regulation was associated with outcomes for emotional problems and conduct problems. More specifically maladaptive emotion regulation strategy such as catastrophising and other blame was closely related with self-reports of emotional problems, likewise other blame, was also linked with scores of conduct problems. This study provides preliminary empirical support for EF and emotion regulation in predicting outcomes of emotional and behavioural problems in children following intervention.